Improving the performance of customer participation in new product development: the moderating effect of social media and firm capabilities. Issue 2 (3rd May 2020) - Jiao, Yuanyuan; Wu, Yepeng; Lu, Qiang Steven
ABSTRACT: Drawing upon the knowledge-based view, this study divides firm knowledge-processing capability (KPC) into market and technical knowledge-processing capabilities, and examines the moderating effect of social media use and two knowledge-processing capabilities on customer participation (CP) in new product development (NPD). The results show that social media use enhances the effect of customer participation on NPD performance (product innovativeness, market performance, and financial performance); firms' two key capabilities (market knowledge-processing capability and technical knowledge-processing capability) further strengthen the moderating effect of social media use. Furthermore, the effect of customer participation on product innovativeness follows an inverted U-shape. This study not only confirms the crucial role of social media use and firm capabilities in customer participation in NPD but also provides firms with theoretical direction for how to use social media.